Untouchable [compact disc, unabridged] - Krentz, Jayne Ann (Recorded Books, 2019)
Jack Lancaster, consultant to the FBI, has always been drawn to the coldest of cold cases. The more cases Jack solves, the closer he slips into the darkness. His only solace is Winter Meadows, a meditation therapist. But as long as Quinton Zane is alive, Jack will not be at peace for long. Having solidified his position as the power behind the throne of his biological family's hedge fund, Zane sets out to get rid of Anson Salinas's foster sons, starting with Jack.